Experimental and numerical investigation of single pores for identification of effective metal foams properties. Issue 5 (26th January 2018) - Heinze, S.; Bleistein, T.; Düster, A.; Diebels, S.; Jung, A.
Abstract: Metal foams are an interesting class of biomimetic materials that are used as lightweight construction elements or as energy absorbers. Foams are micro heterogeneous materials, and the global mechanical properties of a component are strongly affected by the local micro mechanical properties due to a complex structure‐property relationship. The present contribution deals with the identification of effective micro material parameters of aluminum foams from new micro‐compression tests on individual foam pores. Finite element simulations using a fully resolved micro model are applied for parameter identification by inverse calculation. Using the Finite Cell Method, the identified parameters are then used to simulate different pores, so as to reduce the effort of preprocessing by automatically deriving spatial discretizations starting from image‐based models such as CT‐scans. Abstract : Metal foams are an interesting class of biomimetic materials that are used as lightweight construction elements or as energy absorbers. Foams are micro heterogeneous materials, and the global mechanical properties of a component are strongly affected by the local micro mechanical properties due to a complex structure‐property relationship. The present contribution deals with the identification of effective micro material parameters of aluminum foams from new micro‐compression tests on individual foam pores. Finite element simulations using a fully resolved micro model are applied for parameter identification by inverse calculation. Using the Finite Cell Method, the identified parameters are then used to simulate different pores, so as to reduce the effort of preprocessing by automatically deriving spatial discretizations starting from image‐based models such as CT‐scans.